Madrasah Library Human Resources Management Based on Training and Development - Ahmad Husni Hamim; Jaja Jahari; Qiqi Yuliati Zakiyah; Opik Taupik Kurahman; Mohamad Jaenudin (International Journal of Education and Digital Learning (IJEDL), 2025)
The library is an important component in education that functions as a center for information and knowledge sources for students and teachers. Based on literature reviews and initial survey results at two MANs, it was obtained that the competence of library human resources was not supported by knowledge in the field of library science. The placement of library staff is not in accordance with their educational background; therefore, it is necessary to develop HRD of madrasah libraries through education and training for professional staff. The purpose of the study was to identify, analyze, and describe the development of library human resource management planning, implementation of library human resource management, evaluation of library human resource management, strengths and weaknesses of library human resource management, design of an effective training-based library human resource management model in the future with a pattern of HRD development of madrasah libraries based on education and training at MAN 1 Regency and MAN 2 Bandung City. The method used is a qualitative method that uses qualitative data to describe a phenomenon, event, or condition socially. This method is carried out by means of observation, interviews, studying documents. With a qualitative descriptive method to get a picture in the field, explore or photograph the social situation to be studied comprehensively, broadly, and deeply, understand the phenomenon of what is experienced by the research subjects. The successful data is then analyzed to obtain conclusions. The results of this study indicate that there is; First, planning of library human resource management, Second, implementation of recruitment from internal and external library HR based on needs analysis and selection, Third, evaluation of library human resource management by conducting performance assessments, Fourth, identifying the strengths and weaknesses of madrasah library HR, Fifth, designing madrasah HR development which includes planning, organizing, mobilizing, and supervising, Sixth, making efforts to develop library HR through education and training.